Rupture of relational weaves: footprint of corporate synergy - Rivas Montoya, Luz María (Cuadernos de Administración, 2012)
The implementation of processes of synergistic strategies (Ansoff, 1965), inevitably has unforeseen effects on the social organization players. This text presents the relational weave breakdown as a clear example of these effects or traces, which emerged in the storytelling of individual experience that players had with corporate synergy in a leading service sector group in Colombia. From a qualitative method, an ethnographic research strategy and a hermeneutic approach, we explored the experiences and perceptions of various social players. Relational weave breakdown was one of the categories that emerged as a significant footprint; rupture characterized by changes in labor relations, stress autonomy/heteronomy, and power conflicts, situations that express the unintended consequences of implementing shared services integration and corporate synergy. Now it is convenient to note that the main limitation of this exploratory study is that the proposition does not allow constructing models or a methodologically rigorous case study. Complex thinking, from Morin’s (1990) perspective, lit the way for reflection on relational weave breakdown. These weaves are essential in any organization, and more so for multi-business groups where the diversity of businesses and cultures requires networks to make more productive and friendly organizational routines